Dijitalleşmenin yerel gazetelere etkisi : İzmir ve Muş ili örnekleri - Bülbül, Yusuf Özgür (My University, 2023)
Yerel gazeteler, yayım yaptığı coğrafyanın en önemli kitle iletişim araçları arasında yer almaktadır. Yerel gazeteler, iletişim teknolojilerinin gelişmesi ve internetin yaygınlaşmasıyla birlikte yeni bir boyut kazanarak dijitalleşmeye başlamıştır. Dijitalleşme, haberi okuyucuya ulaştırmada yerel gazetelere birçok kolaylık sağlamıştır. Ancak yerel gazeteler, ekonomik ve teknolojik imkânlar bakımından dijitalleşmede farklı düzeyde sorunlar yaşamaktadır. Bu bağlamda dijitalleşmenin yerel gazetelere olan etkilerini araştırmak alan için önem kazanmıştır. Bu çalışma, yerel gazetelerin dijital teknolojinin sağladığı imkânları ne ölçüde kullanabildiğini tespit etmeyi amaçlamaktadır. Çalışmanın birinci bölümünde dijitalleşme ve dijital gazetecilik, ikinci bölümünde yerel gazeteler, üçüncü bölümünde çalışmanın örneklemi olan İzmir ve Muş illerinde gazetecilik ve dördüncü bölümde ise araştırma kısmı yer almaktadır. Gelişmişlik seviyeleri farklı olan İzmir ve Muş ili örnekleri bağlamında incelenen yerel gazetelerden yetkili kişiler ve personellerle yüz yüze görüşmeler gerçekleştirilmiştir. Araştırma bulgularına göre dijitalleşmenin yerel gazeteleri önemli ölçüde etkilediği görülmüştür.

Local newspapers are among the most important mass media in the geography they publish. Local newspapers have started to digitalize by gaining a new dimension with the development of communication technologies and the spread of the internet. Digitization has provided many conveniences to local newspapers in delivering the news to the readers. However, local newspapers experience different levels of problems in digitalization in terms of economic and technological opportunities. In this context, it has become important for the field to investigate the effects of digitalization on local newspapers. This study aims to determine to what extent local newspapers can use the opportunities provided by digital technology. The first part of the study includes digitalization and digital journalism, the second part includes local newspapers, the third part includes journalism in the provinces of İzmir and Muş, which is the sample of the study, and the research part in the fourth part. Face-to-face interviews were conducted with authorized persons and personnel from local newspapers examined in the context of İzmir and Muş provinces with different levels of development. Within the scope of the themes reached through the interviews, it has been observed how digitalization affects local newspapers. According to the research findings, it has been seen that digitalization has a significant effect on local newspapers.
The effect of digitalization on local newspapers : examples of İzmir and Muş provinces
Keywords: Basın; Digital journalism; Digitalization; Dijital gazetecilik; Dijitalleşme; Gazetecilik; Journalism; Local journalism; Local mass media; Lokal newspaper; Press; Turkey; Türkiye; Yerel gazeteler; Yerel habercilik; Yerel kitle iletişim araçları